2013
DOI: 10.1097/jto.0b013e31829ce963
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to EGFR-TKI Can Be Mediated through Multiple Signaling Pathways Converging upon Cap-Dependent Translation in EGFR-Wild Type NSCLC

Abstract: INTRODUCTION For the majority of patients with non-small cell lung cancer, response to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) is suboptimal. In models of acquired resistance to EGFR-TKI, activation of Akt phosphorylation is frequently observed. Since Akt activation results in downstream initiation of cap-dependent protein translation, we hypothesized that a strategy of targeting cap-dependent translation in combination with erlotinib might enhance therapy. METHODS NSCLC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Indeed, induced (Figure S4L) and constitutive (Figure 4H) shedding of EGF as determined by the expression of an EGF-alkaline phosphatase (AP) construct followed by measurement of AP activity in the supernatant revealed decreased EGF shedding in KPn organoids and in Nrf2 -deficient tumor cells (Figure S4M). Consistent with reports showing that EGFR signaling is coupled to activation of cap-dependent translation in EGFR wild type cells (Patel et al, 2013), EGF supplementation was able to restore defective Akt and Erk activation in KPn organoids (Figure S4N). Addition of NAC alone also partially corrected these signaling defects (Figure S4N) and restored EGF release (Figure S4O).…”
Section: Resultssupporting
confidence: 90%
“…Indeed, induced (Figure S4L) and constitutive (Figure 4H) shedding of EGF as determined by the expression of an EGF-alkaline phosphatase (AP) construct followed by measurement of AP activity in the supernatant revealed decreased EGF shedding in KPn organoids and in Nrf2 -deficient tumor cells (Figure S4M). Consistent with reports showing that EGFR signaling is coupled to activation of cap-dependent translation in EGFR wild type cells (Patel et al, 2013), EGF supplementation was able to restore defective Akt and Erk activation in KPn organoids (Figure S4N). Addition of NAC alone also partially corrected these signaling defects (Figure S4N) and restored EGF release (Figure S4O).…”
Section: Resultssupporting
confidence: 90%
“…Here we found that siRNA-mediated Pim-1 knockdown increased the sensitivity of NSCLC cells to cisplatin. Furthermore, EGFR signaling was recently suggested to couple to activation of cap-dependent translation in EGFR wild-type NSCLC cells [ 33 ]. Resistance to EGFR-TKI can be mediated through multiple signaling pathways converging upon cap-dependent translation in EGFR-wild type NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to EGFR-TKI can be mediated through multiple signaling pathways converging upon cap-dependent translation in EGFR-wild type NSCLC. Using an antisense oligonucleotide against eIF4E to disrupt cap-dependent translation can enhance sensitivity to erlotinib [ 33 ]. Interestingly, our present study showed that Pim-1 was involved in the efficacy of EGFR targeted therapies in NSCLC cells with wild-type EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients with lung cancer with wild-type EGFR benefit from EGFR-TKI therapy, 9,10 possibly because resistance to EGFR-TKIs can be mediated through multiple signalling pathways that converge upon cap-dependent translation in NSCLC cells expressing wild-type EGFR. 11,12 Interestingly, our previous study showed that CD73 affected the efficacy of EGFR-targeted therapies in NSCLC cells with wild-type EGFR. 13 Thus, based on the literature, we hypothesized that NRP1 plays a role in the EGF signalling pathway and that knockdown of NRP1 expression might sensitize NSCLC cells to therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%